Musyarakatul Walidaini Lita'limi lughatil arabiyyati fi asri wabai covid-19 - Karimah, Rahmawati; Ahmadi, Ahmadi (Institut Agama ISlam Negeri Palangka Raya, 2023)
Learning is a process of interaction between students and teachers with learning materials, delivery methods, learning strategies, and learning resources in a learning environment. Usually the Indonesian people know that the learning process is a process that is carried out in schools. However, it's different now. The world has created a new history, including changes in the learning system and order. This is caused by the emergence of كوفيد-19 which requires all forms of activities including learning to be carried out from home, one of which is learning Arabic which involves the role of parents in it. This study aims to describe parental involvement in the process of learning Arabic during the كوفيد-19 pandemic taking place in class III MIS Al Jihad Palangka Raya. This study involved five respondents consisting of two parents (key instrument), Arabic subject teacher, and two students (support instrument). The results of this study can be seen that parents are involved in giving attention by motivating, reminding, and supervising. Become a facilitator who provides textbooks, cellphones, wifi, and includes children in tutoring. Become a mentor or mentor who guides and advises children to be responsible in learning. Become a supervisor who always monitors children's learning activities. Be a motivator who always invites children to study every day, and become a communicator who receives and informs everything related to lessons in the student's Arabic learning process which is carried out from home.